1996
DOI: 10.1111/j.1467-8624.1996.tb01745.x
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, Emotional Expressiveness, and Prosocial Behavior

Abstract: Relations between emotional expressiveness, empathy, and prosocial behaviors are important for theoretical and practical reasons. In this study, all 3 areas were assessed across methods and sources. Emotional expressiveness and empathy were evaluated in 73 children in 3 age groups (5‐, 9‐, and 13‐year‐olds) by measuring facial and verbal responses to emotionally evocative videotapes and by ratings from best friends, parents, and teachers. Measures of emotional insight and role taking were also obtained. Prosoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
152
3
25

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(192 citation statements)
references
References 51 publications
12
152
3
25
Order By: Relevance
“…In contrast, an examination of significance tests and effect sizes does not produce consistent evidence suggesting that girls are more likely than boys to report experiencing the same emotion portrayed by hypothetical protagonists (e.g., feeling angry when the protagonist is angry; Dekovic & Gerris, 1994;Feshbach & Feshbach, 1969;Feshbach & Roe, 1968;Hughes, Tingle, & Sawin, 1981; Isannotti, 1986;Roberts & Strayer, 1996). Also, a sex difference in empathy among children and early adolescents was not found in one study employing teacher and friend reports (Roberts & Strayer, 1996). Importantly, though, the accuracy of other-reported empathy is not clear given that empathy is experienced internally.…”
mentioning
confidence: 94%
“…In contrast, an examination of significance tests and effect sizes does not produce consistent evidence suggesting that girls are more likely than boys to report experiencing the same emotion portrayed by hypothetical protagonists (e.g., feeling angry when the protagonist is angry; Dekovic & Gerris, 1994;Feshbach & Feshbach, 1969;Feshbach & Roe, 1968;Hughes, Tingle, & Sawin, 1981; Isannotti, 1986;Roberts & Strayer, 1996). Also, a sex difference in empathy among children and early adolescents was not found in one study employing teacher and friend reports (Roberts & Strayer, 1996). Importantly, though, the accuracy of other-reported empathy is not clear given that empathy is experienced internally.…”
mentioning
confidence: 94%
“…Zhou et al (2002) found that mothers' positive facial expressivity related positively to their child's situational facial and self-reported empathy with positive and/or negative emotions. However, in another study, mothers' facial expressiveness (positive vs. negative expressiveness) while telling a story was unrelated to indices of their children's sympathy or personal distress , and reported maternal positive expressivity has sometimes been unrelated to sympathy .If exposure to high levels of positive emotion helps children experience and express emotion, then they may feel more comfortable feeling others' emotions than children not exposed to positive emotion (Roberts & Strayer, 1996). Parents who express high levels of positive emotion and discuss these emotions may also foster children's understanding and experience of emotion (Eisenberg, Cumberland, & Spinrad, 1998), especially in early childhood (Halberstadt et al, 1999).…”
mentioning
confidence: 94%
“…Empathy refers to the reactions of one individual to the observed experiences of another (Davis, 1983) and implies collective concern and pro-social behavior (Aaker & Williams, 1998;Eisenberg & Fabes, 1990;Roberts & Strayer, 1996). As such, empathy is strongly focused on the collective.…”
Section: Emotions and Attitudesmentioning
confidence: 99%